Walking sideways : the remarkable world of crabs - Weis, Judith S., 1941- (Comstock Publishing Associates, 2012)
"Judith S. Weis provides an engaging and informative tour of the remarkable world of crabs, highlighting their unique biology and natural history. She introduces us to recently discovered crabs such as the Yeti crab found in deep sea vents, explains what scientists are learning about blue and hermit crabs commonly found at the shore, and gives us insight into the lifecycles of the king and Dungeness crabs typically seen only on dinner plates. Among the topics Weis covers are the evolution and classification of crabs, their habitats, unique adaptations to water and land, reproduction and development, behavior, ecology, and threats, including up-to-date research."--Provided by publisher